2017
DOI: 10.3390/ijms18040714
|View full text |Cite
|
Sign up to set email alerts
|

It Is Imperative to Establish a Pellucid Definition of Chimeric RNA and to Clear Up a Lot of Confusion in the Relevant Research

Abstract: There have been tens of thousands of RNAs deposited in different databases that contain sequences of two genes and are coined chimeric RNAs, or chimeras. However, “chimeric RNA” has never been lucidly defined, partly because “gene” itself is still ill-defined and because the means of production for many RNAs is unclear. Since the number of putative chimeras is soaring, it is imperative to establish a pellucid definition for it, in order to differentiate chimeras from regular RNAs. Otherwise, not only will chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 136 publications
(182 reference statements)
0
34
0
Order By: Relevance
“…Moreover, most, if not all, algorithms use only 20 amino acids shown on the genetic code list, despite that there are at least 22 proteinogenic amino acids [ 17 ]. This situation in turn is because we still know too little about translation process, although we have known much more about gene transcription and RNA processes, including RNA splicing [ 2 , 18 , 19 ]. It cannot be ruled out that some of the unmatchable inputs reflect some unknown protein isoforms produced via different mechanisms, such as unknown cis- or trans-splicing derived mRNAs, [ 2 , 18 , 19 ] unknown start or stop codon usage for protein translation, protein splicing, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most, if not all, algorithms use only 20 amino acids shown on the genetic code list, despite that there are at least 22 proteinogenic amino acids [ 17 ]. This situation in turn is because we still know too little about translation process, although we have known much more about gene transcription and RNA processes, including RNA splicing [ 2 , 18 , 19 ]. It cannot be ruled out that some of the unmatchable inputs reflect some unknown protein isoforms produced via different mechanisms, such as unknown cis- or trans-splicing derived mRNAs, [ 2 , 18 , 19 ] unknown start or stop codon usage for protein translation, protein splicing, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This situation in turn is because we still know too little about translation process, although we have known much more about gene transcription and RNA processes, including RNA splicing [ 2 , 18 , 19 ]. It cannot be ruled out that some of the unmatchable inputs reflect some unknown protein isoforms produced via different mechanisms, such as unknown cis- or trans-splicing derived mRNAs, [ 2 , 18 , 19 ] unknown start or stop codon usage for protein translation, protein splicing, etc. In addition, translational errors [ 20 ], which occur more often in cancer cells, may also make some clear inputs unmatchable.…”
Section: Discussionmentioning
confidence: 99%
“…Initially believed to be isolated to blood-based neoplasia (Daley and Ben-Neriah, 1991) and later shown to be common in solid tumors (Barr, 1998;Aman, 1999), fusion transcripts received significant attention due to their diagnostic, prognostic and sometimes remarkable therapeutic implications (Burchill, 2003;Schnittger et al, 2003;An et al, 2010). Discussion of fusion transcripts detected in normal tissues centered on apparently benign events resulting from co-transcription of neighboring genes or more controversially from trans-splicing (Akiva et al, 2006;Peng et al, 2015;Babiceanu et al, 2016;Yuan et al, 2017;He et al, 2018). Reports of fusions in the context of inherited disease existed only in isolated case studies and were not systematically reported on until 2019 (Oliver et al, 2019b).…”
Section: Adapting Fusion Detection To Rare Diseasementioning
confidence: 99%
“…Interestingly, most of these chimeras are formed by RNAs from two neighboring genes on the same chromosome [ 1 , 2 ]. Since this ENCODE report, high-throughput RNA sequencing technology has swiftly spread over all biomedical research and has led to the identification of tens of thousands of chimeric RNAs and other forms of noncolinear RNAs [ 3 , 4 ], as summarized by us previously [ 5 , 6 ]. This number is astonishing, considering that the human genome contains only about 20,000 protein-coding genes [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], although the number of genes may be much larger if noncoding genes are included and if readthrough genomic loci are considered as newly-identified genes and are included, as we have suggested before [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since this ENCODE report, high-throughput RNA sequencing technology has swiftly spread over all biomedical research and has led to the identification of tens of thousands of chimeric RNAs and other forms of noncolinear RNAs [ 3 , 4 ], as summarized by us previously [ 5 , 6 ]. This number is astonishing, considering that the human genome contains only about 20,000 protein-coding genes [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], although the number of genes may be much larger if noncoding genes are included and if readthrough genomic loci are considered as newly-identified genes and are included, as we have suggested before [ 6 ]. Many fusion RNAs derived from fusion genes formed due to genetic alterations [ 15 , 16 , 17 , 18 ], seen mainly in genetic diseases and tumors [ 19 , 20 , 21 , 22 , 23 , 24 ], have also been identified and are, peculiarly, renamed as chimeras, as they also contain sequences of two genes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%